Seroprevalence against the measles virus after vaccination or natural infection in an adult population in Madinah, Saudi Arabia - Waleed H. Mahallawi; Nadir A. Ibrahim (Taylor & Francis Group, 2021)
Background: Over the past few years, measles cases have increased worldwide, despite the availability of a safe and highly effective vaccine. Numerous countries have eliminated measles or have made substantial advancements toward elimination. Materials and Methods: This study investigated the seroprevalence of anti-measles antibodies and vaccination status among 362 men and 81 women in Madinah. All participants were vaccinated or acquired immunity naturally due to infection. We aimed to examine the persistence of anti-measles IgG antibodies, which were qualitatively and quantitatively determined using ELISA. Results: We showed that measles seropositivity (92%, n = 408) was significantly more frequent than negative (5.4%, n = 14) and equivocal results (2.5%, n = 11). Among men, 92.8% were seropositive for the anti-measles IgG antibody, whereas 88.9% of women were seropositive. In addition, a significant relationship was observed between age and measles seropositivity, with a significant positive correlation between age and anti-measles antibody concentration as assessed by Spearman's correlation analysis (r = 0.405, p < .001). Conclusion: Based on these results, observing the serological status of the population 20-38 y after vaccination may be necessary to minimize the proportion of individuals who may be vulnerable to contracting measles. Despite the eﬃcacy of the measles, mumps, and rubella vaccine and the positive global impact associated with the use of this vaccine, including a general decline in measles cases, attention must still be paid to the issue of measles risk, and seronegative individuals should be identified and advised to receive a booster dose of the vaccine.